Quantitative Analysis of Phenolic Acids and Flavonoids in Cuscuta chinensis Lam. by Synchronous Ultrasonic-Assisted Extraction with Response Surface Methodology - Kun-ze Du; Jin Li; Xinrong Guo; Yuhong Li; Yan-xu Chang (Journal of Analytical Methods in Chemistry)
An effective ultrasonic-assisted extraction method for the separation of phenolic acids and flavonoids in Cuscuta chinensis Lam. was conducted by combining uniform design (UD) coupled with response surface methodology (RSM) and orthogonal design (OD) experiment. A sensitive and selective high-performance liquid chromatography-electrospray ionization tandem triple quadrupole mass spectrometry (HPLC-ESI-MS/MS) method was applied to quantify the sixteen active ingredients (chlorogenic acid, cryptochlorogenic acid, neochlorogenic acid, isochlorogenic acid A, isochlorogenic acid B, isochlorogenic acid C, caffeic acid, hyperin, isoquercitrin, quercetin, campherol, p-coumaric acid, isorhamnetin, rutin, astragalin, and apigenin). The extraction method was optimized with respect to concentration of extraction solvent, extraction time, and ratio of liquid to solid as a consequence of getting a high sensitive and feasible method for simultaneous determination of contents of multiple components and evaluation of quality control of Cuscuta chinensis Lam. from different origins. It was also considered useful and valuable in the further study for quality control of Cuscuta chinensis Lam.